2013
DOI: 10.1016/s0254-6272(14)60031-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Yishenjiangzhuo granules on immunity and bone metabolism in patients with stage 3-4 chronic kidney disease

Abstract: In stage 3-4 CKD patients, B cells and IL-17 participated in the induction of osteoclast activation. YJG could also elevate the level of B cells and decrease their apoptosis, but showed no significant effects on active B cells, IL-17 or osteoclast activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In China, TCM has been in practice for thousands of years in the treatment of CRF and has showed number of remarkable results (Lu et al, 2018; Mei, Yang, Wang, & Wang, 2021). Buxu Xiaozheng recipe is a TCM preparation developed by famous and experienced TCM doctors, which previously reported to delay renal interstitial fibrosis progression by modulating the levels of inflammatory factors and oxidative stress in chronic kidney disease patients and rat mesangial cells (Ni, Zhong, & Cai, 2016; Zhong, Wei, & Xing, 2014). C. zedoaria , as the sovereign drug in Buxu Xiaozheng recipe, plays an essential role in the therapeutic effects, in which curcumenol, the major bioactive component in Buxu Xiaozheng recipe isolated from C. zedoaria , has been previously reported to possess neuroprotection, anti‐inflammatory and anti‐tumor effects (Lo, Kamarudin, Hamdi, Awang, & Kadir, 2015; Pintatum et al, 2020), and could be safely used in the assessment of potential pharmacokinetic drug interactions (Sun et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In China, TCM has been in practice for thousands of years in the treatment of CRF and has showed number of remarkable results (Lu et al, 2018; Mei, Yang, Wang, & Wang, 2021). Buxu Xiaozheng recipe is a TCM preparation developed by famous and experienced TCM doctors, which previously reported to delay renal interstitial fibrosis progression by modulating the levels of inflammatory factors and oxidative stress in chronic kidney disease patients and rat mesangial cells (Ni, Zhong, & Cai, 2016; Zhong, Wei, & Xing, 2014). C. zedoaria , as the sovereign drug in Buxu Xiaozheng recipe, plays an essential role in the therapeutic effects, in which curcumenol, the major bioactive component in Buxu Xiaozheng recipe isolated from C. zedoaria , has been previously reported to possess neuroprotection, anti‐inflammatory and anti‐tumor effects (Lo, Kamarudin, Hamdi, Awang, & Kadir, 2015; Pintatum et al, 2020), and could be safely used in the assessment of potential pharmacokinetic drug interactions (Sun et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…[11] The combination of TKSB therapy with Western medicine (WM) can decrease serum creatinine (SCr) and blood urea nitrogen (BUN) and regulate the levels of Ca, P, and PTH. For example, Zheng et al (2012) [12] found that Yishen Jiangzhuo Granule, an effective TCM for TKSB, could significantly improve renal function by decreasing SCr when combined with WM. Zhou (2017) [13] showed that the combination of WM with TKSB therapy could improve the symptoms of kidney failure and reduce bone loss by increasing Ca in blood, reducing P and PTH levels in the blood, increasing bone density, and reducing ALP content.…”
Section: Introductionmentioning
confidence: 99%